Analisis Studi Kasus Dampak Sosiologis terhadap Korban Pelecehan Seksual di Indonesia - Febra Anjar Kusuma; Elsa Aura Savana; Devi, Sandriana; Agustine, Yolanda Fatima (Yayasan Literasi Sains Indonesia, 2025)
Sexual harassment is a complex social issue that has serious psychological, social, and legal impacts on victims. This case study aims to analyze the sociological impact experienced by victims of sexual harassment in Indonesia from the perspective of legal sociology. Using a qualitative approach supported by statistical data, case reports, and legal analysis, this research identifies various contributing factors, multidimensional impacts, and the gap between legal norms and social realities. The findings reveal that sexual harassment not only causes psychological trauma but also leads to changes in social behavior, isolation, loss of self-confidence, and secondary victimization, both in social environments and digital media. Gender inequality, patriarchal culture, and a weak legal system further exacerbate the occurrence of sexual harassment and hinder justice for victims. Therefore, this study emphasizes the importance of victim-centered legal reforms, strengthening social protection systems, increasing legal literacy, and promoting cultural changes within society to prevent and address sexual harassment more effectively and fairly.